Stimulasi Kreativitas Anak Usia 4-5 Tahun Melalui Buku Cerita Bergambar - Nasawa Nurbaiti; Herlinda Herlinda; Afdhal Kusumanegara (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This research aims to analyze the effectiveness of stimulating creativity in children aged 4-5 years through the use of picture story books. Creativity is an important key in developing the potential of early childhood. This creativity can be increased through interesting and interactive learning media. The research method used is classroom action research with qualitative research. Data was obtained through observation and interviews with one of the teachers who teaches at an early childhood education institution. The research results show that the use of picture story books in learning can stimulate children's imagination, creative thinking abilities, encourage children's curiosity, and enrich their vocabulary. Apart from that, the activity of reading together with the assistance of a teacher or parent has a positive impact on children's social interactions. Thus, picture story books can be an effective alternative medium for stimulating the creativity of early childhood children aged 4-5 years.